Using the β-glucosidase catalyzed reaction product glucose to improve the ionic liquid tolerance of β-glucosidases. Issue 1 (December 2016) - Goswami, Shubhasish; Gupta, Neha; Datta, Supratim
Abstract Background Pretreating biomass with ionic liquids (IL) increases enzyme accessibility and cellulose is typically recovered through precipitation with an anti-solvent. An industrially feasible pretreatment and hydrolysis process requires robust cellulases that are stable and active in the presence of either small amounts of ILs co-precipitated with recovered cellulose or for saccharifications in the presence of IL. β-glucosidase (BG) hydrolyzes cellobiose into two molecules of glucose (Glc) and is the last step of biomass hydrolysis. These enzymes are prone not only to product inhibition by glucose but also to inactivation by ILs. With increasing interest in IL-based pretreatment methods, there is increasing focus toward a search for Glc-tolerant and IL-tolerant BG. Results We identified a BG belonging to the GH1 family, H0HC94, encoded in Agrobacterium tumefaciens 5A, and cloned and overexpressed the protein inEscherichia coli. H0HC94 exhibited high enzymatic activity with β-glycosidic substrates (248 µmol/min/mg on pNPGlc and 262 µmol/min/mg on cellobiose) and tolerant to Glc (apparentK i = 686 mM). Further evidence of Glc-based stabilization came from the increase in melting temperature of H0HC94, with increasing Glc concentrations. The half-life of H0HC94 also increased between 2- and 20-fold in the presence of increasing concentrations of Glc. In the presence of 0.9 M of different [C2 mim]-based ionic liquids, the specific activity of H0HC94 decreased by around 20–30 %. However, the addition of 100 mM glucose to the IL-enzyme mix resulted in a more stable enzyme as evidenced by the slight recovery of H0HC94 melting temperature and up to tenfold increase in half-life. This higher stability came at a cost of 2–10 % decrease in specific activity. The steady-state kinetic analyses for a subset of the ionic liquids tested indicate that the enzyme undergoes uncompetitive inhibition by glucose and ionic liquid, indicating the possibility of binding of the ionic liquid and glucose to the enzyme–substrate complex. Conclusions H0HC94 is a Glc-stabilized BG that is also tolerant up to 0.9 M concentrations of different IL's and indicates the possibilities of using an IL–Glc-based cellulose solvent that displays enzyme-compatibility.